Sliding-Window Turbo Equalization and Its Reduced-Complexity Decoding Techniques - Sirawit Khittiwitchayakul; Watid Phakphisut (My University, 2022)
Turbo equalization is a cooperative error-correcting approach to achieve a target bit-error rate over inter-symbol interference channels. In this paper, we proposed a new turbo equalization, called sliding-window turbo equalization (SW-TE), consisting of the Bahl-Cocke-Jelinek-Raviv detector and a spatially coupled, low-density, parity-check decoder. Moreover, the Protograph-based Extrinsic Information Transfer (P-EXIT) chart was modified to investigate the asymptotic behavior of SW-TE. Our analyses showed that SW-TE outperformed conventional turbo equalization in terms of decoding threshold. Based on the P-EXIT chart analysis, we further proposed a guideline of the reduced-complexity decoding techniques for SW-TE, eliminating unnecessary branch metric updates during turbo iterative decoding. Our simulations corroborated the analytical results, showing that SW-TE outperformed conventional turbo equalization while maintaining an acceptable level of complexity.
Keywords: EXIT chart; Turbo; Turbo equalizer; Sliding window protocol; Turbo code; Convolutional code; Error Correcting Code Techniques